Klasifikasi dan Penggunaan Media Pembelajaran: Analisis dan Implementasi dalam Proses Pembelajaran: Analisis dan Implementasi dalam Proses Pembelajaran - Sastafiana, Fina; Eka Saputri, Maharani; Nur Mufidah, Luk Luk (Gerasi Insan Nusantara, 2024)
Learning media is anything that can be used to channel messages from the sender to the recipient so that it can stimulate students' thoughts, feelings, attention and interests in such a way that the learning process occurs. Learning media is very important in the learning process because teachers can convey material to students in a more meaningful way. This research was carried out using a literature review research method which provides output on existing data, as well as an explanation of a discovery so that it can be used as an example for research studies in compiling or creating a clear discussion of the content of the problem to be researched. Based on the types of learning media as quoted and grouped above, learning media can be grouped into several sections [9] as follows (1) print media, (2) exhibition media, (3) audio, (4) visual, (5) ) multimedia, (6) computer. After the type, we move on to the implementation of learning media in the learning process which requires several stages. The following are several stages that are commonly used: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage, (5) evaluation stage.